2022
DOI: 10.1177/15569845221115186
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Mitral Valve Repair: A Guide to Neochordae Reconstruction

Abstract: Mitral valve reconstruction techniques using polytetrafluoroethylene sutures are associated with high repair rates and excellent durability but are dependent on accurate neochordae length estimates. Current strategies to determine the appropriate length of artificial neochordae commonly rely on nonphysiologic saline testing on the arrested heart, with erroneous lengths resulting in residual mitral regurgitation. We present a guide for reproducible and accurate neochordae reconstruction based upon transesophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Patients who underwent MV repair for degenerative MR with a mean gradient greater than 3 mmHg had reduced exercise capacity [29]. Te use of certain valve repair techniques, such as artifcial chordae instead of resection techniques, and the selection of smaller annuloplasty mitral rings, rigid full mitral rings, and excessive utilization of the edge-to-edge technique, were associated with elevated postoperative transmitral gradient and an increased risk of functional mitral stenosis, leading to the long-term hemodynamic deterioration [1,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who underwent MV repair for degenerative MR with a mean gradient greater than 3 mmHg had reduced exercise capacity [29]. Te use of certain valve repair techniques, such as artifcial chordae instead of resection techniques, and the selection of smaller annuloplasty mitral rings, rigid full mitral rings, and excessive utilization of the edge-to-edge technique, were associated with elevated postoperative transmitral gradient and an increased risk of functional mitral stenosis, leading to the long-term hemodynamic deterioration [1,29].…”
Section: Discussionmentioning
confidence: 99%
“…Mitral valve (MV) repair has better long-term results than MV replacement and has been established as the surgical treatment of choice for mitral regurgitation (MR) when the valve lesions are reparable and the procedure is performed at specialized centers with a high rate of successful repairs [1][2][3]. Furthermore, minimally invasive mitral valve repair (MIMVR) has been demonstrated to be safe and efective for MV surgery, providing less morbidity, including stroke, atrial fbrillation, renal failure, and length of stay in carefully selected patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The artificial neochord implantation repair technique, though it is reversible, has its own challenges in length estimation, configuration optimization, and the limited ability to address redundant tissue. [31][32][33][34][35][36] A few studies also reported a large range of artificial neochord numbers, 37,38 yet limited evidence exists regarding the optimal number of artificial neochordae to be implanted for primary MR. Overall, the presence of a large variety of MV repair techniques, which vary greatly in exact deployment details, suggests an important knowledge gap in our understanding of how 1 particular repair technique is better than others.…”
mentioning
confidence: 99%